2011
DOI: 10.1002/hfm.20262
|View full text |Cite
|
Sign up to set email alerts
|

Is implementation of continuous improvement possible? An evolutionary model of enablers and inhibitors

Abstract: The purpose of this article is to present an evolutionary model of the enablers and inhibitors affecting the implementation and sustainability of continuous improvement. With this aim, a qualitative study using the grounded theory was carried out. Interviews were conducted with managers responsible for continuous improvement in first‐tier suppliers in the automotive sector. As a result, two existing lines of research in the continuous improvement literature are synthesized: on one hand, the literature concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 30 publications
0
35
0
8
Order By: Relevance
“…() concluded that employee involvement in lean practices and implementation could prevent negative effects on perceived job autonomy. In addition, García‐Sabater, Marín ‐García, and Perello‐ Marín () argued that employee involvement is an enabler to advance the implementation of continuous improvement. Feedback is also important to achieve creative performance among employees (De Stobbeleir, Ashford, & Buyens, ).…”
Section: Lean Production and Human Resource Practicesmentioning
confidence: 99%
“…() concluded that employee involvement in lean practices and implementation could prevent negative effects on perceived job autonomy. In addition, García‐Sabater, Marín ‐García, and Perello‐ Marín () argued that employee involvement is an enabler to advance the implementation of continuous improvement. Feedback is also important to achieve creative performance among employees (De Stobbeleir, Ashford, & Buyens, ).…”
Section: Lean Production and Human Resource Practicesmentioning
confidence: 99%
“…Yet this is a very enduring and demanding task for managers, one in which it is not easy to succeed. This has motivated several authors like Garcia et al (2014), Garcia-Sabater et al (2012), Dahlgaard-Park (2012) and Bateman (2005), to undertake research regarding the discovery of a series of CI enablers or success factors, all related to the functioning and participation of people inside the organization that could account for the success or failure of different CI initiatives. Although they provide many arguments for including these factors, they failed to provide a comprehensive but concrete list of items inside each of these factors that should be considered by managers in order to monitor EP in CI and its determinants.…”
Section: Determinants Of Employee Participationmentioning
confidence: 99%
“…The importance of having good measures to manage the CI system has been covered in previous CI literature (Jaca, Viles, Mateo, & Santos, 2012;Garcia-Sabater, Marin-Garcia & Perello-Marin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although Board support is fundamental to program design and monitoring, most improvements place at the level of operators and supervisors (Terziovski & Sohal, 2000;García-Lorenzo & Prado-Prado, 2002;García-Sabater, Marín-García & Perelló-Marín, 2012;Jaca, Palpa-Galeano, Viles & Mateo, 2016;Uhrin, Bruque-Cámara & Moyano-Fuentes, 2017). Therefore, staff participation in improvements increases their motivation and satisfaction, (Gerhart, 2012;Wang, Thornhill & Zao, 2016), even as a High Involvement Work Practice.…”
Section: Introductionmentioning
confidence: 99%